Agency and answerability : selected essays - Watson, Gary, 1943- (Oxford : Oxford University Press, 2004)
Charting the progress of Watson's thought over three decades, this collection of essays on human action examines such questions as: in what ways are we free and not free, rational and irrational, responsible or not for what we do
Includes bibliographical references (pages 351-365) and index.
Keywords: Agent (Philosophy); Free will and determinism